Antibacterial effects of natural compounds on biofilm formation of Streptococcus mutans - Farideh Kamarehei; Mohsen Mehdiabadi; Fariba Naderi (Wiley, 2022)
Abstract Streptococcus mutans is the main cariogenic pathogen in the oral cavity, considered to contribute toward oral diseases. S. mutans is predominantly entrapped in plaque biofilms. Objectives In this study, we surveyed the antibacterial activity of natural compounds in terms of the biofilm production of S. mutans. Material and Methods We extracted the studies related to natural compounds affected on S. mutans biofilm from different databases. Results Disruption of S. mutans viability in biofilms by a potent new pharmacological factor could inhibit and remove cavities. Various antibacterial agents are needed to destroy biofilms that remove both pathogens and commensal bacteria, and also exert inhibitory effects on many bacterial species. Conclusions An effective therapeutic agent for dental caries has to be capable of removing pathogens and their biofilms. Specific virulence attributes of S. mutans exist; hence, natural compounds that have excellent properties to combat such pathogens need to be selected.